The Outcome of Patients Requiring Multiple Extracorporeal Membrane Oxygenation: How Many Runs of ECMO is Reasonable?. Issue 6 (June 2016) - Chou, Heng-Wen; Chang, Te-I; Wang, Chih-Hsien; Chou, Nai-Kuan; Chi, Nai-Hsin; Huang, Shu-Chien; Wu, l-Hui; Chan, Chin-Yang; Ponge, Lee-Mei; Wang, Ya-Chen; Chen, Yih-Sharng
Background: Extracorporeal membrane oxygenation (ECMO) has been proven effective in life support for patients with refractory cardiopulmonary failure. Deteriorating patients who have removed their first ECMO support and required second or more courses of ECMO support have rarely been discussed. Methods and Results: All the records of the patients who experienced at least 2 courses of ECMO during single admission were retrieved. Survival was defined as survival to discharge. Demographic data and clinical information were compared between survival and nonsurvival groups. There were 86 patients who received at least 2 courses of ECMO in the 20-year database, and 27 (31.3%) were <18 years old. Of them, 87.3% received 2 runs of ECMO, 10.4% 3 runs, and 2.3% 4 runs. Overall survival rate was 30.2%. The survival rate for patients with 2 runs of ECMO was 33.3% (25 out of 75), 11.1% (1 out of 9) for 3 runs, and 0% (0 out of 2) for 4 runs. Multivariate analysis revealed that only ARF with hemodialysis was the independent risk factor. Conclusions: The decision to perform repeated ECMO implantation is a complex and difficult process. Despite the arguments debating the consumption of resources and increased complications, there are still nearly 1 out of 3 patients who will survive to discharge. More than 2 courses of ECMO may be carefully considered for further rescue.